Characteristics of Clinical Finding in Child Diagnosed with Wilm’s Tumor: A Case Series - Muhammad Ilham Fauzan Patimura; Abdul Azis; Syarif Bakri (Brawijaya Journal of Urology, 2023)
Wilm’s Tumor is the second most common intra-abdominal cancer of childhood, the fifth most common pediatric malignancy overall, and the most common renal tumor in children, representing 95% of all pediatric renal malignancies. However, Most of them present as an asymptomatic abdominal mass. Here we present two cases of Wilm’s tumor with different characteristics of clinical symptoms and ages. In Conclusion, Wilms tumor has a variety of clinical characteristics in each patient. The disease is also frequently found asymptomatically which leads to a delay in diagnosis. Screening for Wilms’ tumor is very important for children who have syndromes or birth defects known to be linked to this disease.